2000
DOI: 10.1021/ac9911490
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Separations of Polar Compounds by Hydrophilic Interaction Chromatography with Evaporative Light Scattering Detection

Abstract: The chiral separations of drug substances and underivatized amino acids were demonstrated in this study through the use of hydrophilic interaction chromatography (HILIC). The polar character of the model compounds presented challenges for their analysis by traditional modes of chromatography, but through the employment of multimodal chromatography utilizing the HILIC mechanism and cyclodextrin- or teicoplanin-derivatized stationary phases, effective resolution was achieved. The analytes lacked sufficient ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 14 publications
0
31
0
3
Order By: Relevance
“…The high density of exposed hydroxyl groups is what makes the CD phases attractive in HILIC. CDs were introduced as ligands in aqueous NPC for the separation of sugar alcohols and mono-, di-, and oligosaccharides as early as 1989 [114], and it is obviously an intriguing phase when the desire is to accomplish chiral separations in HILIC mode [115,116]. In fact, Risley and Strege [115] showed that HILIC is a promising separation mode for polar chiral compounds, as the enantiomers of a compound that separated well in an aqueous ACN eluent in HILIC mode failed to resolve under more conventional, nonaqueous NP conditions on CD or teicoplanin functionalized silicas.…”
Section: Cyclodextrin (Cd)-based Columnsmentioning
confidence: 99%
“…The high density of exposed hydroxyl groups is what makes the CD phases attractive in HILIC. CDs were introduced as ligands in aqueous NPC for the separation of sugar alcohols and mono-, di-, and oligosaccharides as early as 1989 [114], and it is obviously an intriguing phase when the desire is to accomplish chiral separations in HILIC mode [115,116]. In fact, Risley and Strege [115] showed that HILIC is a promising separation mode for polar chiral compounds, as the enantiomers of a compound that separated well in an aqueous ACN eluent in HILIC mode failed to resolve under more conventional, nonaqueous NP conditions on CD or teicoplanin functionalized silicas.…”
Section: Cyclodextrin (Cd)-based Columnsmentioning
confidence: 99%
“…The retention increases with increasing number of monosaccharide units, which is attributed to interactions with the hydrophilic aqueous layer on the exterior of the CD molecules rather than to the penetration of sample molecules inside the cavity (Berthod et al, 1998). CD-bonded columns retain amino acids and some other polar samples more strongly in comparison to the TSKgel Amide-80 phase and are more stable and reproducible than the aminopropyl silica stationary phases (Risley and Strege, 2000).…”
Section: Diol Polyethylene Glycol Thioglycerol Cyclodextrin and Smentioning
confidence: 99%
“…A variety of sugar stationary phases were prepared using the "click" chemistry approach, in which sugar alkynes are covalently coupled to the azido-activated silica gel surface in the presence of a copper catalyst Yu et al, 2009;Santoyo-Gonzalez and Hernandez-Mateo, 2009). The bonded carbohydrates retain their configurations, so that these highly polar stationary phases can be applied to stereoselective separations of monosaccharides and for HILIC separations of highly polar amino acids, glycopeptides, oligonucleotides, and natural products such as flavonoids (Moni et al, 2010).…”
Section: Diol Polyethylene Glycol Thioglycerol Cyclodextrin and Smentioning
confidence: 99%
“…For example, polar pharmaceutical compounds have been successfully analyzed using cyano, amino, and silica stationary phases [13,14]. Enantiomeric separations using CD and macrocyclic antibiotic based stationary phases have also been demonstrated [15,16].…”
Section: Introductionmentioning
confidence: 99%